Reflexões do cuidar e educar na educação infantil: um debate sobre o papel da creche a partir do século XX - BASTOS, Isabeli Cristina Oliveira (2020)
The present Completion of Course Work presents some reflections about the actions of caring and educating in Early Childhood Education, and specifically in the work of daycare centers serving very small children. The reflections of this study subsidized with regard to a historical and legal retrospective of the resized actions the daycare center. From the various researches in the field it can be seen that there’s still a gap between theory and practice regarding work with children in collective spaces. In this sense, in what regulates official laws and documents, care and education must be worked together, however, in the nursery environment, the dichotomization and overlapping of these actions occur in most cases. The problematization of the work refers to the confused relationship between actions and a critique that has been related to the role played by the daycare centers historically, that they have been developing actions with based on welfare concepts, being offered, for the most part, the economically unfavorable population. According to Kramer (2011) in daycare there occurs a compensatory education in which’s a way to assist the poorer population, cognitive stimulation becomes a secondary need. The debate arises with the aim of overcoming the dichotomy between caring and educating, that daycare as an institution that enters the first stage of basic education promotes experiences that fully develop the child being. The objective of this study is to investigate the relationship of caring and educating in Early Childhood Education emphasizing the daycare trajectory in order to find the guiding actions of the work of these institutions. The specific objective’s: to present a retrospective of the historical and legal survey of the daycare center; raise the historical context of the consolidation of daycare in Brazil; discuss how legislation has been organized in daycare regulation; and finally bring the debate through authors about caring and educating in early childhood education. The methodology for the accomplishment of this work was based on a qualitative research and the type of research is Bibliographic Review, that is, for the realization of this reflection of the actions that guide the daycare centers, other works of authors that have already mentioned this subject were used. The result about the reflection has significant advances in pedagogical practices related to daycare, however, there’re some difficulties in which it’s possible to enable the joint work of actions, such as teacher training. This research is important for the exercise of reflection for the practice of professionals who work in collective spaces and who form children.